Благие намерения - Маринина Александра Борисовна (Королева детектива, 2009)
Экземпляры: (20240503) / Инвентарный номер: 34551 / Цена: 365.00 / Сис.шифр: 84(2=411.2)6 / Авт.знак: М 26 / ГРНТИ: 17 / ББК: 84(2=411.2)6